Ligand and p185c-neu density govern receptor interactions and tyrosine kinase activation. - Samanta, A (1994)
The neu protooncogene (also known as c-erbB2, NGL, and HER2) encodes a 185-kDa transmembrane glycoprotein with intrinsic tyrosine kinase activity that resembles the receptor for epidermal growth factor. The p185 gene and protein were originally identified in the brain and are thought to play a critical role in neurogenesis. Aberrant c-erbB2 protein overexpression also occurs in several human adenocarcinomas. A ligand for p185, neu-activating factor (NAF), specifically binds to neu receptor and increases the p185c-neu tyrosine phosphorylation in vitro and in vivo in a dose-dependent manner. We now show that NAF specifically binds to purified p185 expressed in baculovirus. Direct binding analysis showed that NAF binds with high affinity (Kd = 1.3 nM). We have investigated changes in the structure and association state of baculovirus-produced neu holoreceptor that are induced by ligand binding. In this study, we used sucrose gradients to show that purified p185c-neu exists mainly in the monomeric form at low concentrations, whereas at higher concentrations p185c-neu exists as dimers or multimers. At low concentrations, but in the presence of ligand, p185c-neu sediments as a dimeric or multimeric form. Monomer-oligomer interconversion is absolutely ligand dependent at low receptor concentrations. The high molecular weight form of the receptor is enzymatically more active, as a consequence of ligand-driven activation of the receptor kinase. Oncogenic p185neu receptors sediment predominantly as high molecular weight forms and have constitutively active kinases.